Squalamine and Its Derivatives Modulate the Aggregation of Amyloid-β and α-Synuclein and Suppress the Toxicity of Their Oligomers - Limbocker, Ryan; Staats, Roxine; Chia, Sean; Ruggeri, Francesco S.; Mannini, Benedetta; Xu, Catherine K.; Perni, Michele; Cascella, Roberta; Bigi, Alessandra; Sasser, Liam R.; Block, Natalie R.; Wright, Aidan K.; et al. (Frontiers in Neuroscience, 2021)
The aberrant aggregation of proteins is a key molecular event in the development and progression of a wide range of neurodegenerative disorders. We have shown previously that squalamine and trodusquemine, two natural products in the aminosterol class, can modulate the aggregation of the amyloid-β peptide (Aβ) and of α-synuclein (αS), which are associated with Alzheimer’s and Parkinson’s diseases. In this work, we expand our previous analyses to two squalamine derivatives, des-squalamine and α-squalamine, obtaining further insights into the mechanism by which aminosterols modulate Aβ and αS aggregation. We then characterize the ability of these small molecules to alter the physicochemical properties of stabilized oligomeric species in vitro, and to suppress the toxicity of these aggregates to varying degrees towards human neuroblastoma cells. We found that, despite the fact that these aminosterols exert opposing effects on Aβ and αS aggregation under the conditions that we tested, the modifications that they induced to the toxicity of oligomers were similar. Our results indicate that the suppression of toxicity is mediated by the displacement of toxic oligomeric species from cellular membranes by the aminosterols. This study thus provides evidence that aminosterols could be rationally optimized in drug discovery programs to target oligomer toxicity in Alzheimer’s and Parkinson’s diseases.